CHARACTERISTICS OF PHYSICAL FITNESS AND PHYSICAL DEVELOPMENT OF TEENAGERS WITH VISUAL IMPAIRMENT - Voloshyn, O. R. (Rehabilitation and Recreation, 2023)
The system of education and upbringing in secondary schools is currently facing a number of difficulties caused by the introduction of new technologies into the educational process, significant updating of the content of education, changes in the forms and methods of education, the constant complication and intensity of educational programs, and technical re-equipment. The analysis of research indicates a high level of morbidity of various body systems in adolescents, in particular, various diseases of the organs of vision are progressive recently, which is largely due to hereditary factors, low physical activity, the mismatch of the educational load with the biological development of children, as well as a large amount of time spent at the computer. Special attention should be paid to the lack of physical culture and health infrastructure, the restructuring of the network of general education institutions, outdated equipment and sports equipment, limited funds – all this causes a reduction in the amount of physical activity among teenagers. However, practice shows that adolescents who have visual impairments are contraindicated for heavy physical exertion, and, as a rule, at school they belong to a special medical group, this involves the implementation of an individual approach when performing physical exercises and shaping their physical development. The goal is to determine the physical fitness and physical development of visually impaired teenagers. Material and methods. Students of grades 5–11 of Lyceum No. 2 of Drohobytsky district of Lviv region were involved in the research. A total of 75 children were examined, of which 35 were girls and 40 were boys. The following research methods were used, such as: analysis of literary sources, determination of the functional reserve capabilities of the cardiovascular and respiratory systems: (JEL, Skibinska index, Robinson index, Ruffier index). The results. We considered the health of teenagers from the standpoint of their body’s ability to adapt to environmental conditions. It was found that the development and application of complexes of corrective exercises from recreational gymnastics in teenagers with visual impairments provide an opportunity to increase their morpho-functional development and physical fitness, to reduce the level of morbidity of the organs of vision and various systems of the body as a whole. Conclusions. So, the method of using the means of recreational gymnastics allows you to effectively plan physical education classes in special medical groups, they are aimed at preventing visual impairment and improving the functional and physical condition of adolescents, which allows solving both recreational and educational tasks.